Mycenaean civilization, ritual and funerary cult: the case of the PY Tn 316 tablet - Herrera Valenciano, Minor (2023)
In this work, some fundamental aspects related to the beliefs of the Mycenaean civilization regarding the permanence of the soul in the afterlife are analyzed, as well as the performance of cults and rituals in honor of the dead. Special emphasis is given to tablet PY Tn316 for its content, since it is an exceptional document that collects what appears to be a Mycenaean ceremony of sacrifice or offering of human votive offerings to certain deities of the Mycenaean pantheon. This from the detailed study of archaeological, historical and philological evidence. In this way, it turns out that ritual actions are characterized because they are performed considering a certain periodicity and intentionality, for which, in addition, it is a requirement to maintain a special behavior corresponding to the solemnity of the rite, which will manifest itself in a special space and time. This allows us to conclude that reverentiality towards the ancestors, represented in a way that reaches the point of establishing cults in their honor, is closely linked to the concepts of legacy and descent.